Incidence of Ureteric injury in complicated cesarean section and late complications - Hussain , Alaa (University of Thi-Qar Journal of Science, 2015)
Background;Most common operation in gynecological department is c/s ,high percentage of c/s are complicatedresulting with many early and late complication, one of intraoperative complication is ureteric injury and or ureteric ligation.Patients and methods:through 3 years between may 2011- may 2014 on 34 patients get ureteric injury in a complicated C/S discovered either intra operatively or as an early post operative complication with confirm diagnosis by IVU. those patients correct the defect by re anastamosis with ureteric catheterization for two months then fallow up to detect any post operative ipsilateral renal complication.Results:We get 26 patient (76.4%) was complain from intermittent ipsilateral renal symptoms , repeated U/S showing ipsilateral mild dilated PCS with chronic U.T.I in general urine examination.Conclusion:Ureteric injury may lead to chronic complaining of the patients from chronic U.T.I and a sequence ofureteric stenosis , so we advise that in any complicated C/S we need a urosurgical doctor in addition to the gynecologist surgeon to avoid as much as possible ureteric injury.Aim of study:To assess the incidence of ureteric injury with a complicated C/S.